Decentralized SISO Active Disturbance Rejection Control of the Newell-Lee forced circulation evaporator. Issue 8 (2015) - Dittmar, Rainer
Abstract: Active Disturbance Rejection Control (ADRC) has received considerable attention in recent years as an effective tool for advanced control practitioners to solve control problems for nonlinear uncertain systems. This paper presents results of a simulation study for the control of an evaporator system benchmark, when a multiple linear ADRC control structure is used, and the controllers are designed based on first and second order linear models approximating the process dynamics. In addition to the control performance under nominal conditions, the robustness with respect to plant-model mismatch is studied. The major advantage of ADRC compared to MPC and PI control approaches is the simple and transparent tuning, and that only a coarse process model is sufficient for the design. For a broader industrial application of ADRC in the process industries, user-friendly off-line design tools as well as real-time ADRC control software for PLCs and DCS still have to be developed.